Modelling, analysis and validation of wireless controller area network. (2016) - Mary, Gerardine Immaculate; Alex, Zachariah C.
The controller area network (CAN) is the pioneer in standardising vehicle and automation bus standards. For the wired CAN to meet the emergent pervasive wireless technology, wireless controller area network (WCAN) is introduced. WCAN is based on wireless token ring protocol (WTRP); a MAC protocol for wireless networks to reduce the number of retransmissions due to collision and the wired counterpart CAN attribute on message-based communication. CAN uses token frame method to provide channel access to the nodes in the system. This method allow all the nodes to share common broadcast channel by taken turns in transmitting upon receiving the token frame which is circulating within the network for specified amount of time. This method provides high throughput in bounded latency environment, consistent and predictable delays and better packet delivery ratio. WCAN is tested by simulation using QualNet and compared with IEEE 802.11 and is found to outperform it in ring network. The test results are validated using SAE benchmark.